A study on improvement of tool life using a heat shield in laser assisted machining to Inconel 718. (October 2021) - Jeong, Ho-In; Lee, Choon-Man
Highlights: Tool life of laser assisted machining (LAM) and LAM with heat shield were evaluated. The depth of cut and tool temperature was analyzed by finite element analysis. The processing efficiency was analyzed of LAM and LAM with heat shield compared. Abstract: When aerospace materials such as nickel and titanium-based alloys are machined using conventional machining methods, productivity is very low because of the excessive tool wear and high cutting forces. However, in this study, the machineability of high-strength materials such as Inconel 718 is dramatically improved by using laser assisted machining (LAM) with heat shielding applied. The novel combination of LAM and heat shield is shown to improve the tool life and reduce the thermal energy applied to tool by laser heat source. In addition, processing quality is higher than LAM. Moving laser heat source analysis was performed to obtain the appropriate depth of cut for the LAM and the thermal effect of the tool due to the heat shield application. Experiments for tool life analysis were carried out under the same material removal rate (MRR) according to the application of the heat shield. Finally, changes in tool life and machining efficiency due to application of heat shield, and effectiveness of heat shield, are detailed.